THE INFLUENCE OF DIFFERENCES COOKING METHOD OF COCKLE (Anadara granosa) ON PROTEIN CONCENTRATE QUALITY - Beri Prima Panjaitan; Edison Edison; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aim of this study was to determine the difference cooking method of cockles (Anadara granosa) on protein concentrate quality. The method used in this research was experimental method, which was comparing boiling and steaming method to the quality of cockle protein concentrate. The quality parameters test in this research were yield, moisture, protein and fat content. The all data were analyzed using the T-test. The results showed that the yield value of boiled cockle meat (390 g/19.4%), shell (1.470 g/73.4%) and impurities (140 g/6.8%). The yield of steamed cockle meat (476 g/23.8%), shell (1.364 g/68.2%) and impurities (160 g/8%). The mean value of yield of boiled cockle protein concentrate was 74.44 g/16.68% and steamed (80.94 g/17.38%). The mean value of proximate analysis of boiled cockle protein concentrate on meat for moisture, protein, and fat content was 5.70%, 72.98% and 0.29%, and for steamed was 4.75%, 74.97%, and 0.59%, respectively. Keywords: cockle, protein concentrate, boiling, steaming